Implementasi Program Keluarga Harapan (PKH) di Dusun Pasar Tambunan Desa Lumban Pea Kecamatan Balige Kabupaten Toba - Bertua Daely; Tuti Atika (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The Family Hope Program (PKH) is the provision of conditional social assistance to Poor Families (KM) who are designated as PKH beneficiary families. As a conditional social assistance program, PKH opens access to poor families, especially pregnant women and children, to take advantage of various health service facilities and education service facilities available around them. The purpose of this research is to find out how the implementation of the Family Hope Program in Pasar Tambunan Hamlet, Lumban Pea Village, Balige District, Toba Regency. This research data collection technique is by literature study, observation, interviews, and documentation. Based on this research, it is known that the suitability between the program and the beneficiaries can be said to be achieved because the beneficiary families are greatly helped by the assistance of the family hope program. The suitability between the program and the implementing organization in the process of implementing the program and supervision of the implementing organization in accordance with the guidelines. The compatibility between the beneficiary group and the implementing organization can be said to be achieved because the family hope program assistants and social service people are very friendly to the beneficiary families and routine assistance is carried out every month.